2002
DOI: 10.1021/jp020585e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Double Bond Position on Dehydroergosterol Fluorescence Intensity Dips in Phosphatidylcholine Bilayers with Saturatedsn-1 and Monoenoicsn-2 Acyl Chains

Abstract: We have investigated the spectroscopic evidence for sterol superlattice formation in bilayers composed of dehydroergosterol (DHE) and a homologous series of phosphatidylcholine, namely, C(18:0):C(18:1∆ n )PC with n ) 6, 7, 9, 11, and 13. These phosphatidylcholines (PCs) possess the same number of carbons and the same number of cis double bonds; however, the position of the double bond of these PCs varies. We have examined the fractional concentration dependence of the steady-state fluorescence intensity of DHE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
(115 reference statements)
3
5
0
Order By: Relevance
“…A comparison of TRF data obtained for liposomes prepared by the dry film method revealed that the data scatter was signifi-cantly higher than when the LTT method was used (results not shown). Nevertheless, the critical X CHOL 's observed in the present study agree favorably with those observed previously using the dry film method Sugar, 2002, Wang et al, 2002), perhaps because an extensive temperature recycling-incubation protocol was employed in the latter case (Chong and Sugar, 2002).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A comparison of TRF data obtained for liposomes prepared by the dry film method revealed that the data scatter was signifi-cantly higher than when the LTT method was used (results not shown). Nevertheless, the critical X CHOL 's observed in the present study agree favorably with those observed previously using the dry film method Sugar, 2002, Wang et al, 2002), perhaps because an extensive temperature recycling-incubation protocol was employed in the latter case (Chong and Sugar, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…All of the above critical cholesterol contents, except the one at 0.55, agree favorably (within 60.03) with the SL compositions of 0.20, 0.33, 0.40, and 0.50 predicted by the SL model (Virtanen et al, 1995;Somerharju et al, 1999;Chong and Sugar, 2002). In agreement with previous fluorescence studies on cholesterol SL using different probes (Tang et al, 1995;Chong et al, 1996;Chong and Sugar, 2002;Wang et al, 2002), these TRF results provide strong support for the proposition that cholesterol may adopt regular, superlattice-like distributions in fluid lipid bilayers. Since POPC, rather than a fully saturated PC was used here, the present data might be relevant for natural membranes as well.…”
Section: Abrupt Changes In Physical Properties Of Dph-pc Occur At Many Critical Cholesterol Concentrations Predicted By the Sl Modelsupporting
confidence: 90%
“…Our interpretation of the source of this interaction (i.e., acyl chain entropy contribution) is consistent with the experimental observation that superlattices do not form in a gel-phase bilayer, in which entropy change should be minimum. In addition, it is also consistent with the finding that the double bond position on acyl chains can affect cholesterol superlattice formation (Wang et al, 2002). Wang and Chong discovered that if a cis double bond is located between C9 carbon and the carboxyl carbon of acyl chains, superlattices become undetectable.…”
Section: Delicate Balance Of Interactionssupporting
confidence: 85%
“…Our observation that the double bonds have little effect on x à chol value is not totally surprising. Recently, Wang et al (2002) measured the formation of cholesterol superlattices at low cholesterol concentration using fluorescence measurements. They found that cholesterol superlattice becomes undetectable when the cis double bond of PC is located at the same level of cholesterol steroid ring, i.e., between C8 and the carboxyl carbon.…”
Section: Maximum Solubility Of Cholesterol In Dopcmentioning
confidence: 99%
“…Furthermore, in some mixtures of fluid-phase phospholipids and cholesterol, evidences suggest that cholesterol molecules can form regular distribution domains (e.g., hexagonal or centered rectangular pattern superlattices) to maximize the cholesterol-cholesterol sepa-ration Virtanen et. al., 1995;Liu et al, 1997;Wang et al, 2002;Cannon et al, 2003).…”
Section: Introductionmentioning
confidence: 99%